Utilization of Infrastructure for Accessibility of Students with Disabilities in Inclusive Junior High Schools - Sina, Ibnu; Suparmi, Suparmi (Department of Special Education, 2025)
This study aims to analyze the contribution of school infrastructure in supporting accessibility and learning quality for students with physical disabilities at junior high school (SMP Negeri 24 Surakarta). A qualitative descriptive approach was used with data collection through interviews and observations of five key participants, namely teachers, school staff, special assistant teachers, and students with disabilities. The research findings indicate that the school already has some important facilities, such as ramps, accessible toilets, and classrooms that are easily accessible by wheelchair. However, limitations were still identified, particularly regarding access to upper floors and the absence of handrails on ramps. The school is gradually improving its facilities to create a more inclusive learning environment. This study emphasizes that the development of physical infrastructure, accompanied by policy support and teacher training, is an important step in achieving fair and inclusive education for all students